'At home at Oxbridge': British views of ancient Greek sport 1749–1974. Issue 2 (3rd April 2021) - Carter, Andy
ABSTRACT: Elite British education in the second half of the nineteenth century was often dominated by the Classics inside the classroom and a culture of manly athleticism outside. Given this combination, it was natural that, some scholars turned their attention to sport in the ancient world. By marrying accounts from ancient literature with the evidence emerging from new archaeological discoveries, figures such as Percy Gardner and E. Norman Gardiner were able to create detailed and compelling pictures of ancient sport which were accepted as definitive for much of the following century. The world they described was surprisingly familiar, as were the concerns they flagged up about contemporary sport based on the alleged pitfalls of antiquity. In recent decades their work has been extensively reassessed in terms of the accuracy of their analysis of original Greek and Roman sources and the claims they concerning the Hellenic roots of athletic amateurism. This paper analyses the environment and connections of British historians of ancient sport from the mid-eighteenth to the mid-twentieth century to understand how their perceptions of the past were shaped by the concerns of their present, leading them to effectively 'write themselves' into their work.